Black, Young & Conduct Disordered: Extrapolating Scott Henggeler’s Multisystemic Psychotherapy Paradigm for the Attenuation of At-Risk Behaviors of Black Youth in North America - Ogbuagu, Buster C. (European Scientific Journal, ESJ, 2018)
Problem Statement: More than any other racial category, Black Youths have experienced severe racial disparities in contravention, trial and incarceration rates, the moment they come in contact with law enforcement agencies. There is a growing amount of literature suggesting that implicit racial biases do indeed exist in those who enforce the law, especially when such enforcers have limited time or and lacked cultural competencies to process their actions. These disparities are troubling, especially on account of the fact that although Black Youth comprise 16 percent of all children in America, yet they account for 28 percent of all juvenile arrests (National Council on Crime & Delinquency, 2007). It is not to imply that Black youths do not commit crimes. They do, just like all other ethnically diverse populations. However, there are research findings that Black youth pay a rather heavy premium for engaging in criminal or anti-social behaviors, mostly on account of their race, socioeconomic backgrounds, which are saturated by the stereotypical absence of a father or father figure, matriarchies, poverty and being mired in poor neighborhoods on one hand and on the other, a criminal justice system that disproportionately targets them. Approach: The paper applied an extrapolation of Scott Henggeler’s Multisystemic Psychotherapy paradigm to evaluate how its application can assist in stemming Black Youth lemming-like rush into the juvenile and criminal justice systems. It utilized secondary data analysis and literature on Black youth, juvenile, criminal justice and conduct disorders to evaluate this therapeutic approach in a Large Group Intervention-LGI setting. Result: Research indicate that the Multisystemic Therapy approach had previoulsy been applied at a micro level with satisfactory outcomes. In this case, I propose a treatment paradigm intended to be extrapolated [from Henggeler’s approach] to a Large Group Intervention-LGI and community setting, using all the parameters as Henggeler and team enunciated, but with slight adjustment and modifications to fit a Large Group Intervention target audience. Conclusion: The successful application of Hengeler’s Therapeutic Model within a Large Group Intervention setting significantly attenuated negative Black Youth interaction within the criminal justice systems in the USA, Canada and elsewhere. Additionally, successful application of this paradigm enhanced Black Youth pro-social skills for the development of the self, community and the nation states where Black Youths call home.